Pasarse + gerundio como verbo seudocopulativo. Un análisis sincrónico con datos de Lima, Perú - Martel Paredes, Víctor Arturo (El Colegio de México, 2023)
In this paper I present an analysis of the frequentative verbal periphrasis pasarse + gerund. I offer a description and analysis of the pronominal clitic in pasarse, characterized as middle voice; I discuss the obligatory nature of a depictive gerund, due to the desemantization of pasarse, and its significance as an aspectual pseudo-copulative that connects the subject with a stage-level predicate; and I examine the selection of a complement of time, corresponding to a complement, not of event, but of aspect. I conclude that these characteristics point to a void of lexical content and to the predominance of functional features of aspect.